c-di-GMP Homeostasis Is Critical for Heterocyst Development in Anabaena sp. PCC 7120 - Huang, Min; Zhang, Ju-Yuan; Zeng, Xiaoli; Zhang, Cheng-Cai (Frontiers in Microbiology, 2021)
c-di-GMP is a ubiquitous bacterial signal regulating various physiological process. Anabaena PCC 7120 (Anabaena) is a filamentous cyanobacterium able to form regularly-spaced heterocysts for nitrogen fixation, in response to combined-nitrogen deprivation in 24 h. Anabaena possesses 16 genes encoding proteins for c-di-GMP metabolism, and their functions are poorly characterized, except all2874 (cdgS) whose deletion causes a decrease in heterocyst frequency 48h after nitrogen starvation. We demonstrated here that c-di-GMP levels increased significantly in Anabaena after combined-nitrogen starvation. By inactivating each of the 16 genes, we found that the deletion of all1175 (cdgSH) led to an increase of heterocyst frequency 24 h after nitrogen stepdown. A double mutant ΔcdgSHΔcdgS had an additive effect over the single mutants in regulating heterocyst frequency, indicating that the two genes acted at different time points for heterocyst spacing. Biochemical and genetic data further showed that the functions of CdgSH and CdgS in the setting-up or maintenance of heterocyst frequency depended on their opposing effects on the intracellular levels of c-di-GMP. Finally, we demonstrated that heterocyst differentiation was completely inhibited when c-di-GMP levels became too high or too low. These results together indicate that the homeostasis of c-di-GMP level is important for heterocyst differentiation in Anabaena.